A case-control study about markers of stress in normal-/overweight women with polycystic ovary syndrome and in controls - Marschalek, Marie-Louise; Marculescu, Rodrig; Schneeberger, Christian; Marschalek, Julian; Dewailly, Didier; Ott, Johannes (Frontiers in Endocrinology, 2023)
Background: Polycystic ovary syndrome (PCOS) is linked to an elevated risk of psychological disorders, decreased quality of life and emotional distress. Serum cortisol as a potential stress marker has been found to be increased in women with PCOS. The aim of this study was to evaluate both saliva stress markers and subjective psychological distress in women with PCOS. Methods: In a prospective case-control study, 31 PCOS women and 31 healthy controls were included. Salivary cortisol, chromogranin A and metanephrines were collected in the morning and in the evening. Emotional distress and quality of life were assessed by means of the Perceived Stress Scale-10 (PSS-10) and the Short form-36 (SF-36). Multivariate generalized linear models were applied to test the influence of various parameters on numerical outcome parameters. Results: After correction for age and body mass index (BMI), there were no statistically significant differences of salivary biomarkers between PCOS women and healthy controls (p>0.05). PCOS patients revealed significantly higher increased PSS total scores and lower quality of life in all SF-36 modules apart from pain (p< 0.05). The PSS total score was positively correlated to prolactin in PCOS women (r= 0.450; p= 0.011). In overweight/obese PCOS patients, a higher BMI, a higher Ferriman Gallwey score and higher age significantly predicted the PSS total score (p< 0.05). Conclusion: Stress measured by salivary biomarkers did not differ between PCOS women and healthy controls, whereas stress scores evaluated by questionnaires were significantly greater in women with PCOS. A higher BMI, hirsutism and a higher age seem to be main modulators of subjective stress in PCOS. Prolactin might serve as a biomarker for chronic stress in PCOS women.